Sköld och spjut: judisk apologetik och polemik visavi kristendomen och de kristna i Frankrike och Spanien 1100–1500 - Kronholm, Tryggve (Nordisk judaistik/Scandinavian Jewish Studies, 1990)
This article is a review of the dissertation Shield and sword. Jewish polemics against Christianity and the Christians in France and Spain from 1100 to 1500 by Hanne Trautner-Kromann. The purpose of the dissertation is to describe and explain Jewish polemics against Christianity and the Christians in France and Spain in the period between the first crusade and the expulsion of the Jews from Spain.